Transient Tics and Tourette's Syndrome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1988)
The relation of transient tic disorder (TTD - motor or vocal tics lasting less than 1 year) to Tourette's syndrome (TS multiple motor and vocal tics lasting longer than 1 year) has been evaluated in two Canadian Mennonite families at the Dept of Neurology, Univ of Rochester Sch of Med, NY.